2009
DOI: 10.1074/jbc.m807600200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Contributes to the Maintenance of Contractile Force in Human Ventricular Cardiomyocytes

Abstract: Prolonged Ca2؉ stimulations often result in a decrease in contractile force of isolated, demembranated human ventricular cardiomyocytes, whereas intact cells are likely to be protected from this deterioration. We hypothesized that cytosolic protein kinase C (PKC) contributes to this protection. Prolonged contracture (10 min) of demembranated human cardiomyocytes at half-maximal Ca 2؉ resulted in a 37 ؎ 5% reduction of active force (p < 0.01), whereas no decrease (2 ؎ 3% increase) was observed in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…mTORC2 also plays a role in cardiac hypertrophy, 10 since it controls the actin cytoskeleton and activates Akt and PKCα, which has been shown to maintain contractile force by associating with troponin I in myocytes. 34 The effect of mTOR on the expression of both fetal and constitutive hypertrophy genes is not well understood. However mTORC1 and 2 may contribute to the hypertrophic changes observed in the hypercholesterolemic myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC2 also plays a role in cardiac hypertrophy, 10 since it controls the actin cytoskeleton and activates Akt and PKCα, which has been shown to maintain contractile force by associating with troponin I in myocytes. 34 The effect of mTOR on the expression of both fetal and constitutive hypertrophy genes is not well understood. However mTORC1 and 2 may contribute to the hypertrophic changes observed in the hypercholesterolemic myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, the increase in myofilament-associated PKC␣ following an acute ischemic challenge may also represent a compensatory change. Molnar and colleagues (46) found that PKC␣ maintains cardiac myofilament force development under conditions that occur during I/R. By contrast, ShintaniIshida and Yoshida (55) report that post-I/R activation of PKC␣ at the sarcoplasmic reticulum exacerbates I/R damage, arguing for subcellular-specific effects of PKC␣.…”
Section: Discussionmentioning
confidence: 99%
“…Among the isoforms that are activated by overexpression of FGF2 in the mouse heart that may also phosphorylate targets modulating cardiac function are PKCε and ␣ (1,5,9,17,22,27,33,34,46,53). PKCε has been shown to localize to the cross-striated structures when activated (17, 27, 52) and is known to phosphorylate troponin I (TnI) and troponin T (TnT), as well as myosin light chain and myosin binding protein C (MyBP-C), which modulates calcium sensitivity of the myofilaments in the heart (34).…”
mentioning
confidence: 99%
“…37 Dempsey et al 38 found that cardiac myocytes contain at least six different PKC isozymes but preconditioning results in activation of only two isozymes, PKC-d and PKC-e. Quantitation of PKC-isoform expression showed the dominance of the Ca 2+ -dependent PKCa over PKC-d and PKC-e. PKC-a is the single isozyme that translocates to the contractile system on Ca 2+ stimulation in the rat heart, suggesting a unique physiological role for PKCa in the Ca 2+ -dependent regulation of myofibrillar contractility. 39,40 The a-subunit of Gq is a well-established mediator of hypertrophic growth in neonatal cardiomyocytes and in mouse hearts. Studies have found that although aortic AR-a 1A , AR-a 1B and AR-a 1D are associated with Gqa, AR-a 1B is also linked to Goa and the couple AR-a 1B -Goa mediates the contractile response of rat aorta.…”
Section: Discussionmentioning
confidence: 99%